Smart Forest Security and Monitoring System - Prasad Ramchandra Mavarkar; Jayachandra C; Bharat Gadivaddar; Spoorti Magadum; Kavya Huggi; Ranjita H (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Trees are the most important of our planet, not only in forest but also in countless another ecosystem. trees play an important role in maintaining biodiversity & providing food & Habitat for countless microorganism, The objective of this project is recognizing the enemy of the most important robbery in the forest regions. The theft & illegal development of commercial trees such as Sandalwood, Teak, Sagwan etc. these trees are the most valuable in the world. This is used in medical science & in addition beauty care products because of the carge amount of money Involve in such sales of tree trunks & many indicates occurs by cutting a type & their smuggling.